Face Recognition using Webcam with K Nearest Neighbors Algorithm for Employee Presence - Nurul Akbar Tanjung; Sanwani Sanwani (STMIK Budi Darma, 2021)
Attendance is an activity to store data related to employee attendance. Therefore, it is necessary to have a presence with a biometric identification system such as facial identification so that the presence can run quickly and at a low cost. Attendance system helps employees and companies to run attendance faster and cheaper. The K Nearest Neighbor algorithm has a function as a classification algorithm in machine learning. The K value which is the highest accuracy by reaching 100% is 4 people with the determination of K equal to 3